The interplay between iron accumulation, mitochondrial dysfunction, and inflammation during the execution step of neurodegenerative disorders - Urrutia, Pamela J.; Mena, Natalia P.; Nunez, Marco T. (Frontiers in Pharmacology, 2014)
A growing set of observations points to mitochondrial dysfunction, iron accumulation, oxidative damage and chronic inflammation as common pathognomonic signs of a number of neurodegenerative diseases that includes Alzheimer's disease, Huntington disease, amyotrophic lateral sclerosis, Friedrich’s ataxia and Parkinson’s disease. Particularly relevant for neurodegenerative processes is the relationship between mitochondria and iron. The mitochondrion upholds the synthesis of iron-sulfur clusters and heme, the most abundant iron-containing prosthetic groups in a large variety of proteins, so a fraction of incoming iron must go through this organelle before reaching its final destination. In turn, the mitochondrial respiratory chain is the source of reactive oxygen species (ROS) derived from leaks in the electron transport chain. The co-existence of both iron and ROS in the secluded space of the mitochondrion makes this organelle particularly prone to hydroxyl radical-mediated damage. In addition, a connection between the loss of iron homeostasis and inflammation is starting to emerge; thus, inflammatory cytokines like TNF-alpha and IL-6 induce the synthesis of the divalent metal transporter 1 and promote iron accumulation in neurons and microglia. Here, we review the recent literature on mitochondrial iron homeostasis and the role of inflammation on mitochondria dysfunction and iron accumulation on the neurodegenerative process that lead to cell death in Parkinson’s disease. We also put forward the hypothesis that mitochondrial dysfunction, iron accumulation and inflammation are part of a synergistic self-feeding cycle that ends in apoptotic cell death, once the antioxidant cellular defense systems are finally overwhelmed.